Comparison of Immunochromatography Method and Immunocytochemistry Method in Rapid Detection of NS-1 Antigen in Dengue Infection - How Tien Jack; Sitti Rahmah Umniyati; Elsa Herdiana Murhandarwati (Pusat Kedokteran Tropis, 2013)
ABSTRACT Introduction: Rapid test kit based on immunochromatography test (ICT) in detecting dengue NS-1 antigen for early dengue infection is available in the market. Its availability allows earlier management for dengue infected patient but it remains costly to most people. Recently, Dengue Team of Universitas Gadjah Mada has developed monoclonal antibodies to detect the presence of dengue NS-1 antigen in leucocytes of infected patients based on Streptavid in Biotin Peroxidase Complex (SBPC) immunocytochemistry method.Objectives: The objective of this study is to determine the validity of the immunochromatography (SD Dengue NS1 Ag) method by determining kappa agreement index between two observers, and to compare the diagnostic performances of ICT and immunocytochemistry methods in detecting dengue NS1 antigen in the blood samples.Methods: A cross sectional study design is used. This study uses 35 blood plasma remains from a previous study conducted on RT-PCR method. Three drops of blood plasma were added into the well of SD Dengue Duo NS1 and results were read after 15-20 minutes. The diagnostic performances of ICT which defined by sensitivity, specificity, positive predictive value and negative predictive value were calculated and compared to secondary data of immunocytochemistry result from the same blood samples, with reference of RT-PCR as a gold standard. A McNemar’s test was conducted and p value less than 0.05 was considered as significant different.Result: Detection of dengue infection by using SD Dengue NS1 Ag has strong agreements between two observers with kappa value of 1, and the sensitivity of 50%, specificity of 91%, positive predictive value of 92% and negative predictive value of 45% with reference of RT-PCR as a gold standard. Meanwhile sensitivity and specificity value of the immunocytochemistry test were 88% and 100% respectively, and the positive and negative predictive values were 100.0% and 70.0% respectively with reference of RT-PCR as a gold standard. The immunocytochemistry assay showed overall accuracy of 91,0%.Conclusion: Immunochromatography (SD Dengue NS1 Ag) method to detect NS-1 antigen has less sensitivity and specificity compared to SBPC immunocytochemistry method.Keyword: Immunocytochemistry, Immunochromatography, Streptavidin Biotin Peroxidase Complex (SBPC), NS-1 Ag, dengue